(untitled) (REVISTA NODO, 2021)
This text reviews the current state of nature on the planet and the anthropogenic causes of the incumbent ecological crisis. The review illustrates essential elements of the ecologic functioning and a contemporary paradigm to understand the surrounding space as a landscape, formed by metabolic and cultural terms. The text combines anthropocentric perspectives with views independent from man’s presence to link the disruptions of the metabolic regime of the biosphere to the human act of dwelling. The final agenda proposes five imperatives relative to the spheres of cognition, demography, economy, ecology, and built environment, meant to revert the ongoing ecological crisis on the planet.